The design of mobile numerical application development lifecyle for children with autism - Naziatul Shima, A.A. (Penerbit UTM Press, 2016)
Children with autism require special attention during the teaching and learning process. The use of information technology in special education can assist the teaching and learning process become more effective. Many applications were developed to enhance the social skills and communication skills of the children with autism as they are known with social and communication impairments. However, numerical skills are also important to prepare the children for lifelong learning. Yet, the children with autism are struggling with normal learning methods. For that reason, a mobile numerical application is proposed to assist the children with autism to acquire numerical skills. The development of the numerical application adapted ADDIE lifecycle which consists of five phases; analysis, design, development, implementation and evaluation. This paper objectively discusses a design phase for development lifecycle of mobile numerical application, developed for the children with moderate and mild autism who are learning basic numbers, basic shapes and size of objects. The design phase of the numerical application uses the deliverable from the analysis phase which had been completed previously. This paper discusses the learning theories, learners and usability which have been incorporated in designing the numerical application. Heuristic evaluation had been conducted with three evaluators to improve the user interface of the mobile numerical application. The results from the heuristics evaluation show all the evaluators agreed and strongly agreed with all heuristics. Constructive suggestions were also obtained from the evaluators. The development phase of the mobile numerical application would be carried out in future. Â© 2016 Penerbit UTM Press. All rights reserved.